Morphometric Analysis and Stress Orientation of Kaba, Daun, and HulupalikVolcanoes, Bengkulu Province, Indonesia - Dadin Mars Abimayu Abimayu; Arif Ismul Hadi Hadi; Refrizon; Nanang Sugianto; Sapari Dwiyono; Andre Rahmat Al Ansory; Hana Raihana Raihana; Arieffin Yusuf Hakim Hakim; Asy Syifa Auliya Putri Ramadhani (Jurnal Fisika, 2024)
Bengkulu Province is an area in Sumatra that is surrounded by Bukit Barisan. This research aims to provide information about the horizontal stress orientation data σHmaxs on the volcanoes of Kaba, Bukit Daun, and Hulupalik, as well as added information about the slope data in the research location that underlies the volcanic arc on the Sumatra Fault. We conducted this research by mapping the morphology of the mountain and determining the straight line of stress orientation, this research uses DEMNAS data of Geospatial Information Agency (BIG). At Kaba Mountain, the maximum stress azimuth angle (σHmaxs) is orientated towards 62° to the East-Northeast/ENE. The direction of plate movement that gives horizontal stress on Kaba volcano is from the east-northeast / ENE and west-southwest / WSW. On Mount Hulupalik determining the azimuth angle of the orientation of the Horizontal stress σHmaxs, the azimuth is towards NNE29°. On Mount Daun where the azimuth angle itself is NNE26°. From the azimuth direction of the horizontal stress (σHmaxs) of Mount Daun and Hulupalik, the plate stress moves from South Southwest/SSW and North Northeast/NNE. Regardless of the direction of horizontal stress/σHmaxs of each mountain, it is influenced by several factors that can cause different stress directions.